Impact of suboptimal neoadjuvant chemotherapy on peri‐operative outcomes and survival after robot‐assisted radical cystectomy: a multicentre multinational study. (18th November 2016) - Hinata, Nobuyuki; Hussein, Ahmed Aly; George, Saby; Trump, Donald L.; Levine, Ellis G.; Omar, Kawa; Dasgupta, Prokar; Khan, Muhammad Shamim; Hosseini, Abolfazl; Wiklund, Peter; Guru, Khurshid A.
Abstract : Objectives: To evaluate the effect of suboptimal dosing on the outcomes of patients who received neoadjuvant chemotherapy (NAC) and robot‐assisted radical cystectomy (RARC). Patients and Methods: We retrospectively reviewed 336 consecutive patients with urothelial carcinoma of the bladder who were treated with NAC and RARC at three academic institutions. Outcomes were compared among three groups: patients who received optimal NAC; patients who received suboptimal NAC; and those who did not receive NAC. To adjust for potential baseline differences between the three groups, propensity‐score‐based matching was performed. The suboptimal dose group was defined as those who received <3 cycles of cisplatin‐based chemotherapy, received a decreased dosage, or those not treated with cisplatin. Primary outcomes analysed were recurrence‐free survival (RFS) and overall survival (OS). Secondary outcomes were peri‐operative complications and readmissions after RARC. Results: After propensity‐score matching, 69 patients in the cohort received optimal‐dose NAC, 41 received suboptimal NAC and 69 did not receive NAC. Complication rates and readmission rates did not differ significantly among the three groups. On multivariable analysis, suboptimal NAC and no NAC were independent predictors of worse RFS (hazard ratio [HR] 2.5, 95% confidence interval [CI] 1.2–5.7, P = 0.01 and HR 2.4, 95% CI 1.28–5.16, P = 0.01) and worse OS (HR 4.5, 95% CI 1.6–15.0, P < 0.01 and HR 4.9, 95% CI 1.9–15.6, P < 0.01) in patients who received NAC and RARC. Failure to achieve pathological complete response (ypT0N0) was also an independent predictor of worse RFS (HR 6.6, 95% CI 1.3–20.9; P = 0.02) and OS (HR 4.9, 95% CI 1.8–15.3; P = 0.02). Conclusion: Optimal NAC resulted in a better RFS and OS when compared with suboptimal or no NAC. Suboptimal and no NAC were associated with worse OS and RFS. These findings will facilitate improved patient counseling and treatment selection.